ACTIVATION OF DIFFERENT CEREBRAL FUNCTIONAL REGIONS FOLLOWING ACUPUNCTURE AT BOT H TAIXI AND TAICHONG ACUPOINTS AND TAIXI ACUPOINTALONE: AN FMRI STUDY - Wang, Y.J.; Zheng, Y.; Zhang, G.F.; Zhang, J.P.; Wu, C.X.; Zhang, S.Q.; Ouyang, H.L.; Li, Z.P; Chen, J.R.; Qu, S.S.; Chen, J.Q.; Huang, Y.; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: To explore the brain function regions characteristics of the acupoint combination, this study observed activity changes in the brain regions of healthy volunteers after acupuncture at both Taixi (KI3) and Taichong (LR3) (KI3 + LR3) and KI3 alone using resting-state functional magnetic resonance imaging (fMRI). Methods and Materials: 30 healthy volunteers were randomly allocated into two groups, one group received acupuncture at KI3 and LR3, the other only acupuncture at KI3, 15 cases in each group. All volunteers underwent resting-state fMRI of the brain 15 minutes before acupuncture, and which the needle was retained in place for 30 minutes; 15 minutes after withdrawing the needle underwent a further session of resting-state fMRI. The amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) were used to analyze the changes in brain regions. Results: The KI3+LR3 group compared with the KI3 group, the ALFF analysis indicated that the brain changes relatively concentrated in BA 2, 3, 7, 8, 9, 10, 18, 19, 20, 31, 32, 40, 46 and the cerebellum posterior lobe, the ReHo analysis indicated that the brain changes relatively concentrated in BA 4, 6, 7, 10, 11, 18, 19, 20, 21, 22, 31, 40 and the cerebellum posterior lobe. Conclusion: Based on this study, compared with acupuncture at KI3, acupuncture at KI3 + LR3 which could specifically influence BA 7, 10, 18, 19, 20, 31, 40 and cerebellum posterior lobe, which may be related to synergy mechanism of two acupoints combination treatment.